Surfactant Free Preparation of Celecoxib Microcrystals by a Controlled Precipitation Process - Sepideh Mardani, Maryam Maghsoodi, Hamed Hamishehkar (Tabriz University of Medical Sciences, 2017)
Background: The antisolvent precipitation technique has evolved into an effective method to prepare microcrystals of drug. Although this method has advantages, such as cost effectiveness, the processing is significantly sensitive to stabilizer. The aim of present study was to prepare celecoxib (CLX) microcrystals via antisolvent precipitation technique without any surfactants. Methods: Acetone was used as a solvent for the CLX and water was used as an antisolvent. During the precipitation process, several experimental parameters, such as the volume ratio of antisolvent to CLX solution, the concentration of CLX solution, the temperature and the stirring speed, were investigated. Results: The results showed that external characteristics such as particle size and its distribution were strongly influenced by the process parameters, while the internal structures such as chemical composition and crystal structure were unaffected during the process. Higher volume ratio of antisolvent to CLX solution, lower temperature and more- intense stirring led to the smaller crystals. However, increasing the concentration of CLX solution resulted in aggregation of crystals and consequently formation of large crystals with more heterogeneous distribution. It was found that this effect could be prevented by using of ethanol as co-solvent with volume ratio to acetone 5:1. Under the optimum conditions, the yielded powder had a mean particle size of 7 µm and 70 % of the particles were distributed in the range of 0.3- 15 µm. Conclusion: Results of this study offer a useful starting point for a conceptual framework to guide the preparation of microcrystals without using a stabilizer.